1977
DOI: 10.1080/17450397709434275
|View full text |Cite
|
Sign up to set email alerts
|

Langfristige Fütterung von Azetylharnstoff an Milchkühe

Abstract: After an introductory survey of investigations dealing with the conversion of acetyl urea in the ruminant organism, a feeding trial using dairy cattle is described in which the effects of long-term acetyl urea feeding on the clinical picture and various performance parameters have been studied. Five Black-Pied cows of medium milk yield were fed a natural diet and received, over at least 14 months, a daily acetyl urea supplementation of 430 g (= 40 to 44% of the digestible crude protein). The clinical control, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These authors speculate that observed improvements in digestibility were due to N recycling back to the rumen. Attempts to manage the N release rate of dietary urea in the rumen with other forms of NPN (Bergner, Görsch, Wiesner, & Willer, 1977) suggests that N supply to the rumen may have been through rumeno-hepatic circulation, as proposed earlier (Egan & Moir, 1965). This body of work provides the first evidence that supplying the rumen with a source of N derived from endogenous circulation via post-ruminal NPN supplementation may be an efficient approach to facilitate fibre digestion and ruminal stability.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These authors speculate that observed improvements in digestibility were due to N recycling back to the rumen. Attempts to manage the N release rate of dietary urea in the rumen with other forms of NPN (Bergner, Görsch, Wiesner, & Willer, 1977) suggests that N supply to the rumen may have been through rumeno-hepatic circulation, as proposed earlier (Egan & Moir, 1965). This body of work provides the first evidence that supplying the rumen with a source of N derived from endogenous circulation via post-ruminal NPN supplementation may be an efficient approach to facilitate fibre digestion and ruminal stability.…”
Section: Discussionmentioning
confidence: 74%
“…The first proposal to use amines as a method to encourage carbohydrate digestion in the ruminant was made more than a century ago (Zuntz, 1891) and later examined and verified as an effective NPN supplementation strategy (Hart, Bohstedt, Deobald, & Wegner, 1939). Attempts to manage the N release rate of dietary urea in the rumen with other forms of NPN (Bergner, Görsch, Wiesner, & Willer, 1977) suggests that N supply to the rumen may have been through rumeno-hepatic circulation, as proposed earlier (Egan & Moir, 1965). Additional studies described the effects of short-term duodenal infusion of urea in sheep fed low-protein, high-forage diets, showing improvements in feed intake and digestibility as well as improved N balance (Egan, 1965;Egan & Moir, 1965).…”
Section: Discussionmentioning
confidence: 99%